2019
DOI: 10.1111/trf.15591
|View full text |Cite
|
Sign up to set email alerts
|

Risk of piperacillin‐induced hemolytic anemia in patients with cystic fibrosis and antipseudomonal treatment: a prospective observational study

Abstract: BACKGROUND Drug‐induced immune hemolytic anemia (DIIHA) is a rare but severe side effect caused by numerous drugs. Case reports and case series suggest that piperacillin‐related DIIHA may be more common among patients with cystic fibrosis (CF). However, the prevalence is speculative. The aim of this prospective, observational study was determine the prevalence of DIIHA in such affected patients. METHODS AND MATERIALS Patients with CF hospitalized for parenteral antibiotic therapy at Charité Universitätsmedizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…With the exception of tazobactam, which causes IHA via the nonionic protein absorption pathway, all other drugs cause IHA via the drug-dependent antibody pathway. 15,26,27 Using FAERS database data for disproportionality analysis, we identified some rarely reported drugs, such as lisdexamfetamine, escitalopram, diazepam, aripiprazole, ribavirin, quetiapine, buprenorphine, ribavirin, and peginterferon alfa-2a. Although these drugs might cause IHA rarely, they still should be of concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of tazobactam, which causes IHA via the nonionic protein absorption pathway, all other drugs cause IHA via the drug-dependent antibody pathway. 15,26,27 Using FAERS database data for disproportionality analysis, we identified some rarely reported drugs, such as lisdexamfetamine, escitalopram, diazepam, aripiprazole, ribavirin, quetiapine, buprenorphine, ribavirin, and peginterferon alfa-2a. Although these drugs might cause IHA rarely, they still should be of concern.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of tazobactam, which causes IHA via the nonionic protein absorption pathway, all other drugs cause IHA via the drug-dependent antibody pathway. 15,26,27…”
Section: Discussionmentioning
confidence: 99%
“…A review of prior studies and reports showed that piperacillin-tazobactam-induced hemolytic anemia is more common in patients with cystic fibrosis, which may be attributed to their repeated exposure to recurrent infections [ 6 , 7 ]. A recent study has reported an instance of piperacillin-tazobactam-induced pancytopenia in a neonate.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced immune hemolytic anemia (DIIHA) is a side effect of medication that can cause serious consequences. The annual incidence of DIIHA with obvious anemia is 1–4 per million people [ 1 3 ]. The mechanism of DIIHA is due to the immune damage to red blood cells (RBCs) caused by drug-induced antibodies (including drug-dependent antibodies and/or drug-independent antibodies) or non-immunologic protein adsorption (NIPA) [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%